THE EFFECT OF SMART BOXES ON ELEMENTARY SCHOOL STUDENTS’ KNOWLEDGE OF EARTHQUAKE DISASTER PREPAREDNESS - Hidayati, Nur; Lutfihani, Sri Aninda Heptya; Maghfuroh, Lilis (Jambura Nursing Journal, 2026)
School-age children are vulnerable to the impact of disasters due to their lack of understanding and knowledge about earthquake preparedness. To increase children’s disaster preparedness knowledge, an attractive learning media smart boxes can be employed. This study aims to analyze the effect of smart box education on students’ knowledge of earthquake disaster preparedness. The research design was a quasi-experiment with two groups and a pre-post-test control group. The population consisted of 180 elementary school students, selected by cluster random sampling, with 130 students involved in the study (65 in the intervention group and 65 in the control group). Data were collected using an earthquake preparedness knowledge questionnaire. The intervention group received smart box education, while the control group received lecture-based education. The pre- and post-tests were conducted on the same day. The study took place on February 27, 2025, at Madrasah Ibtidaiyah Muhammadiyah Sedayulawas in the Brondong District of the Lamongan Regency. The data were then analyzed using Wilcoxon and Mann-Whitney tests (α ≤ 0.05). The results showed that 60% of students had poor knowledge before receiving smart box education while after receiving smart box education, 58.5% of students had good knowledge. Providing smart box education and lecture media increased students’ knowledge about earthquake disaster preparedness (p=0.000), with an average score of 25.77 in the intervention group and 4.77 in the control group. Smart box education proved to be more effective than lectures in increasing students’ knowledge of earthquake preparedness because smart boxes encourage critical thinking and hands-on learning, whereas lectures only require students to listen.